Assessment of variation in antioxidative defense system in salt-treated pea (Pisum sativum) cultivars and its putative use as salinity tolerance markers - Noreen, Zahra (Journal of plant physiology, 2009)
The present work describes whether the changes in the activities of antioxidant enzymes and the levels of some non-enzymatic antioxidants could be used as markers of salt tolerance in nine genetically diverse pea (Pisum sativum) cultivars. All cultivars were exposed to four levels of NaCl i.e., 0, 40, 80 and 120mM in sand culture. Plant fresh biomass, total phenolics, total soluble proteins, hydrogen peroxide (H(2)O(2)), malondialdehyde (MDA), superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in leaves while different forms of tocopherols (alpha-, gamma- and Delta-tocopherol) in fresh seed of salt-stressed and non-stressed plants were analyzed. On the basis of percent inhibition in shoot biomass at the highest salt level (120mM) cultivars 2001-35, 2001-55 and Climax were ranked as tolerant (percent inhibition less than 60%), 2001-20, 9800-5 and 9800-10 moderately tolerant (percent inhibition 60-70%), and 2001-40, 9200 and Tere 2 salt sensitive (percent inhibition more than 70%). Salt stress markedly enhanced the activities of SOD and POD, levels of total phenolics and gamma- and Delta-tocopherols, and decreased the total soluble proteins and CAT activity, while the internal levels of H(2)O(2) remained unaffected in all pea cultivars. Although salt-induced oxidative stress occurred in all pea cultivars, the response of salt-tolerant and salt-sensitive cultivars with respect to the generation of enzymatic and non-enzymatic metabolites measured in the present study was not consistent. Of different antioxidant enzymes and metabolites analyzed, only CAT activity was found to be a reliable marker of salt tolerance in the set of pea cultivars examined